Ethanol and formic acid as synergistic solvents for converting lignite to platform chemicals. (1st June 2021) - Li, Zhan-Ku; Cheng, Jin-Yuan; Yan, Hong-Lei; Lei, Zhi-Ping; Yan, Jing-Chong; Ren, Shi-Biao; Wang, Zhi-Cai; Kang, Shi-Gang; Shui, Heng-Fu
Highlights: Ethanol and FA with different roles synergistically enhanced the conversion of XL. The maximum yield of ESP was obtained at 300 °C with FA to ethanol ratio of 1:10 mL/mL. Phenols, arenes, and esters can be produced from FA-catalyzed ethanolysis of XL. Yields of phenols and arenes increased to ca. 2–5 times with adding FA to ethanolysis of XL. Abstract: Formic acid (FA)-catalyzed ethanolysis of Xilinguole lignite (XL) was carried out with FA to ethanol ratio of 0–1:6 mL/mL at 220–320 °C. The optimal conditions were determined to be 300 °C and FA to ethanol ratio of 1:10 mL/mL based on ethanol-soluble portion (ESP) yield and the maximum ESP yield is 48.0 wt%. Both carbon balance and Fourier transform infrared spectrometric analyses confirm that FA and ethanol involved in ethanolysis of XL. Three major platform chemicals, i.e., arenes, phenols, and esters, were identified in ESPs by gas chromatography/mass spectrometry. The yields of arenes and phenols significantly increased from 15.67 to 58.33 mg/g and 36.02 to 168.44 mg/g with adding FA to ethanolysis of XL, respectively. The alkyl groups of arenes and phenols are more abundant in ESPs from FA-catalyzed ethanolysis of XL. The results suggest that FA enhanced hydrogenolysis of aryl ethers and alkylation of ethanol during XL ethanolysis. Hydrogen generated from FA hindered dehydrogenation of ethanol, resulting in the decrease of ethanol-derived esters. Ethanol acts as in-situ hydrogen donor for hydrogenolysis and reactant for alkylation, aldol condensation, and esterification, while FA serves as acid catalyst and in-situ hydrogen donor for hydrogenolysis. Additionally, possible pathways for FA-catalyzed ethanolysis of XL were proposed.